Gossamer-like V2O5 Thin Films for the Detection of Toxic Volatile Organic Compounds - Ravinder, G.; Sreelatha, C. J.; Chandar rao, P.; Nagaraju, P.; Vijayakumar, Y.; Sreekanth, T. (Journal of Scientific Research, 2021)
Nanostructured vanadium pentoxide (V2O5) thin films are successfully deposited on an ultrasonically cleaned glass substrate with different deposition parameters via spray pyrolysis technique. The X-ray diffraction analysis showed that the V2O5 films are polycrystalline with an orthorhombic structure. SEM analysis illustrated that the gossamer-like morphology at the substrate temperature of 325 °C. The average crystallite size of the films changes from 14.29 to 23.81 nm, due to the deposition temperature enhancement. The film which is deposited at a substrate temperature of 325 °C has shown high transmittance. XPS studies validated the existence of V5+ oxidation form of vanadium in vanadium oxide thin film. Gas sensors are electronic devices designed to trace the concentration of different toxic gases existing in the environment. Gas sensing characterization has been performed using static liquid distribution technique towards different volatile organic compounds such as acetone, methanol, toluene and xylene. The thin film prepared at a substrate temperature of 325 °C has shown the maximum response towards 100 ppm of toluene at room temperature. The response and recovery times are determined using transient response curve, and the obtained values are 21sec and 31sec, respectively.